Efficacy of a modified cranial closure technique with bone cement in reducing postoperative complications following microvascular decompression surgery: a retrospective cohort study - Shilong Wang; Jun Li; Jiangtao Dong; Ganggang Wang; Haoxiang Xu; Licang Zhu; Lina Pan; Hui Xu (European Journal of Medical Research)
Abstract Background This study aimed to assess the efficacy of a modified cranial closure technique combined with bone cement in mitigating postoperative complications, particularly cerebrospinal fluid (CSF) leakage, following microvascular decompression (MVD) surgery. Methods A retrospective analysis was conducted on 234 patients who underwent MVD surgery at our institution from October 2017 to October 2024. The patients were divided into three groups based on closure methods: autologous bone with bone cement and titanium screw and plate (ABBC + TSP), autologous bone with bone cement (ABBC), and traditional cranial closure (TCC). Postoperative complications, including CSF leakage, intracranial infection, and subcutaneous effusion, were compared among the groups. Results The incidence of CSF leakage was significantly lower in the modified groups (ABBC + TSP and ABBC) compared to the traditional group (2.5% and 1.8 vs. 27.0%, P < 0.001). Multivariate logistic regression analysis confirmed that the modified technique was an independent protective factor against CSF leakage (OR 0.138, p = 0.024). Additionally, the modified groups demonstrated significantly lower rates of intracranial infection, subcutaneous effusion, and postoperative headache (p < 0.05). Conclusion The modified cranial closure technique combined with bone cement significantly reducing postoperative complications in MVD surgery, particularly CSF leakage and intracranial infection, presenting a promising approach for optimizing surgical outcomes.